Patient Characteristics, Clinical Courses, Fatality Rates, Predictors of Severe Diseases, and Deaths in Intensive Care Unit: A Lebanese Retrospective Cohort of COVID-19 Patients - Hachem , Mohamad; Chahine, Yaacoub; Nassif, Elissa; Haddad, Georges (International Journal of Clinical Research, 2022)
Background: The novel coronavirus 2019 (COVID-19) pandemic is straining Intensive Care Units’ (ICU) capacities worldwide. It was demonstrated that the ICU mortality rate from Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) is higher than from other viral pneumonia. Aim: The goal of this research is to determine ICU COVID-19 patient characteristics, clinical courses, fatality rates, as well as risk factors for severe diseases and mortality in Lebanon, a country known to suffer from a deficiency in ICU capacity as well as a high COVID-19 infection rate. Methods: We conducted a retrospective monocentric cohort study that enrolled COVID-19 patients admitted to the ICU at Baabda Governmental Hospital, between January 1, 2021, and March 31, 2021. Demographics, clinical, radiological, laboratory characteristics, treatments, and medical and infectious complications were gathered and compared between survivor and non-survivor groups, as well as between mild/moderate and severe/septic groups. Parameters were then entered in a multivariate regression analysis to identify predictors of death and disease severity. Results: A total of 191 patients were included in our study. The fatality rate reached 35.6% in our population with a median ICU length of stay of 8 days. Non-survivors were more likely older (p<0.001), active smokers (p=0.008), and in severe or septic stage at admission (p<0.001). Elevated levels of neutrophils (p=0.013), ferritin (p=0.002), lactate dehydrogenase (p<0.001), and C-reactive protein (p=0.008) were more frequently encountered in non-survivors. The latter were more commonly intubated (p<0.001) and suffered from complications such as ventilator-associated pneumonia, sepsis, cytokine storm, myocardial infarction, and pulmonary embolism (p<0.001). Multivariate analysis showed that older age, intubation, and severe/ septic stage at admission were associated with an increased risk of death. Conclusion: Older COVID-19 patients who were intubated, and those who were in severe or septic stages at ICU admission